ANALISIS PENGARUH DANA ZAKAT, INDEKS PEMBANGUNAN MANUSIA, DAN KEMISKINAN TERHADAP LAJU PERTUMBUHAN EKONOMI JAWA BARAT DENGAN PENDAPATAN PERKAPITA SEBAGAI VARIABEL INTERVENING PERIODE TAHUN 2014-2019 - Widya Permatasari (JURNAL EKONOMI, 2021)
This study aims to determine the effect of zakat funds, human development index, and poverty on the economic growth rate of west java with percapita income as an intervening variable for the 2014-2019 period. This research is quantitative research with a sample of 27 provinces in west java and ovtained 125 data in the 2014-2019 observation period. Based on the results pf the test conducted, it shows that the zakat variable was has a positive and significant effect on economic growt. The Human Development Index has a positive anad significabt effect on economic growth. The poverty variable has a negative and significant effect on economic growth. Per capita income variable has a positive and significant effect on economic growth. The zakat variable has a positive and significant effect on per capita income. The human development index variable has a positive effect on per capita income. Poverty variable has a negative and insignificant effect on per capita income. Keywords: Dana zakat, Indeks Pembangunan Manusia, Kemiskinan, Pertumbuhan Ekonomi, Pendapatan Perkapita.